Spatial variation in the technical and qualitative condition of the housing stock: Evidence from the 2021 National Population and Housing Census - Horynek, Hubert (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
The aim of this study is to determine the scale and spatial distribution of potential exclusions from the housing stock in Poland, based on the 2021 National Census data contained in the Local Data Bank, distinguishing between technical exclusions (resulting from the durability of buildings) and qualitative exclusions (resulting from insufficient equipment of dwellings with basic installations). Each value was calculated for counties. Based on a review of the relevant literature, it was assumed that the average useful life of residential buildings is 100 years. The quality of the housing stock was calculated based on the level of equipment with installations (running water, bathroom, gas, flushable toilet). The analysis confirmed that the vulnerability of the housing stock to exclusions varies significantly across Poland, driven by both technical and qualitative factors that do not clearly overlap. In a broader perspective, the findings of this study can provide a foundation for designing territorially differentiated programs for renovation and modernization of housing stock and contribute to improving decision-making processes in housing policy at the local and regional levels.